Comparison results for solutions to the anisotropic Laplacian with Robin boundary conditions. (January 2022) - Sannipoli, Rossano
Abstract: In this paper we consider PDE's problems involving the anisotropic Laplacian operator, with Robin boundary conditions. By means of Talenti techniques, widely used in the last decades, we prove a comparison result between the solutions of the above-mentioned problems and the solutions of the symmetrized ones. As a consequence of these results, a Bossel–Daners type inequality can be shown in dimension 2.